2018 IEEE International Conference on Pervasive Computing and Communications Workshops (PerCom Workshops) 2018
DOI: 10.1109/percomw.2018.8480369
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Negative Emotions During Real-Life Driving via Dynamically Labelled Physiological Data

Abstract: Driving is an activity that can induce significant levels of negative emotion, such as stress and anger. These negative emotions occur naturally in everyday life, but frequent episodes can be detrimental to cardiovascular health in the long term. The development of monitoring systems to detect negative emotions often rely on labels derived from subjective self-report. However, this approach is burdensome, intrusive, low fidelity (i.e. scales are administered infrequently) and places huge reliance on the veraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Previous studies have similarly proposed optimal HRV features for stress monitoring [10,11,12,13,14,15,16]. However, most of those studies considered a singular exposure to a specific stressor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have similarly proposed optimal HRV features for stress monitoring [10,11,12,13,14,15,16]. However, most of those studies considered a singular exposure to a specific stressor.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, a feature selection approach such as the filter [13,14] and wrapper method [13,15,16] was used for determining optimal HRV features. Aigrain et al [15] evaluated the predictive power of various multimodal features by investigating the composition of the best feature subset and showed that the HR values (maximum and variation) and the amplitude of HR (maximum, mean, and variation) provided the best prediction among features related to ECGs.…”
Section: Related Workmentioning
confidence: 99%
“…A custom-made version of the conventional Tetris was adapted to create real-time adjustments of the game difficulty in three levels by using a SVM classifier that processed signals from skin response, blood volume and EEG (Chanel et al, 2011). Furthermore, learning-based classifiers have also been used to detect high and low anxiety in drivers from ECG and accelerometer data (Dobbins and Fairclough, 2018), or to create a virtual driving platform to maximize engagement in people with autism spectrum disorder (Bian et al, 2019). Applications for airplane pilots used classifiers to identify features from EEG and skin response signals that can model the users in scenarios of attention-related human performance limiting states (Harrivel et al, 2016) or to find relationships of cardiovascular features with psychophysiological stress while performing piloting maneuvers (Hanakova et al, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…Although comparing the emotional model of human beings with an emotional model of animals is not perfect, in this paper, they were compared to check the feasibility and the effectiveness of the model. The emotion detection models implemented in the human considered the physiological signals as the primary input for the identification of emotional state [46,47]; those data were missing in our emotion detection model. One of the findings was that the relationship between body language pattern and emotional state described by [48], could be compared to our model because tail wagging is considered a decoded version of body language [49].…”
Section: Discussionmentioning
confidence: 99%